2011
DOI: 10.1371/journal.pone.0016658
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sulfated Polysaccharides Disrupt Cathelicidins, Inhibit RAGE and Reduce Cutaneous Inflammation in a Mouse Model of Rosacea

Abstract: BackgroundRosacea is a common disfiguring skin disease of primarily Caucasians characterized by central erythema of the face, with telangiectatic blood vessels, papules and pustules, and can produce skin thickening, especially on the nose of men, creating rhinophyma. Rosacea can also produce dry, itchy eyes with irritation of the lids, keratitis and corneal scarring. The cause of rosacea has been proposed as over-production of the cationic cathelicidin peptide LL-37.Methodology/Principal FindingsWe tested a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 44 publications
0
74
1
Order By: Relevance
“…However, most studies that suggest RAGE as a receptor for LL37 provide indirect evidence [5,12,13]. Nevertheless, we observed that the LL37-induced interleukin-8 production by human bronchial epithelial cells can be partly inhibited by RAGE-antagonistic peptide (data not shown).…”
contrasting
confidence: 57%
“…However, most studies that suggest RAGE as a receptor for LL37 provide indirect evidence [5,12,13]. Nevertheless, we observed that the LL37-induced interleukin-8 production by human bronchial epithelial cells can be partly inhibited by RAGE-antagonistic peptide (data not shown).…”
contrasting
confidence: 57%
“…To test whether RAGE was required for IsoLG-PE-induced signaling, we examined the effect of two RAGE antagonists with differing modes of action on IsoLG-PE activation of macrophages. We found that GM-0111, a synthetic glycosaminoglycan previously shown to act as an RAGE antagonist (73), significantly inhibited IsoLG-PE-induced NFjB reporter activity (Fig. 7B).…”
Section: Identification Of Receptor For Advanced Glycation Endproductmentioning
confidence: 76%
“…27 In addition, both LL-37 and RAGE are highly elevated in patients with chronic sinonasal inflammation. 9,23 This pathway is not unique to the sinuses, as the RAGE pathway has been elucidated in many other chronic inflammatory diseases, including, but not limited to, rosacea, 27 arthritis, 42 and interstitial cystitis. 30 Further investigations are needed to define LL-37-RAGE induced upper airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…21,27 Heads were bisected in a sagittal plane at the nasal septum and the mucosa evaluated for gross differences. The bisected sections were randomly assigned to either histology/immunohistochemistry or sinus tissue processing.…”
Section: Methodsmentioning
confidence: 99%